Interactive Multimedia Learning on the Basis of Problem Based Learning (PBL) for Vocational High School (VHS) Students - n, Khairudi; Suryani, Karmila; Widyastuti, Rini; Setiawan, Anugerah (International Journal of Engineering and Technology, 2018)
This research is aimed at producing a valid, practical and effective interactive multimedia learning on the basis of problem-based learning. The product is designed to help teachers and students in better understanding of school subject: â€œPeripheral Functions and PC Installationâ€. The study is conducted by applying research and development method with the following stages: potential problem localization, data collection, product designing, design validation, performance test, product revision, and final testing and commissioning. After performing content validity test by taking into account expertsâ€™ theory, and conducting practicality test by distributing questionnaires to the users, as well as effectiveness test by giving examinations to the participants, it can be found the following percentages of the respective tests, namely: 88.06% for validity test; which is a good criterion, 85.03% for practicality test; which is a practical criterion, and 88.04% for effectiveness test; which is also a good criterion. Such results show that the interactive multimedia learning on the basis of problem-based learning may be said to have been valid, practical and effective